Evaluation of Aceh Special Autonomy Policy on Human Resource Development - Mukhrijal; Nofriadi; Nurul Kamaly; Fitri Rahmalija; Humairah Fatin Sausan; Ismi Masthura Mawardi; Rini; Zikra Ul Khaira (Social and Political Corner, 2026)
This study aims to evaluate the implementation of Aceh's Special Autonomy policy in developing Human Resources, specifically through an analysis of the planning, governance, and effectiveness of the use of the Special Autonomy Fund. The research focuses on the education and health sectors, as well as community competency improvement programs, which are priorities for Aceh's Human Resource Development. The research approach uses a qualitative method with in-depth interviews and documentation techniques. Informants include the Aceh Regional Development Planning Agency as the development planning coordinator, health workers at Community Health Centers, and the community as beneficiaries. The results show that the Special Autonomy Fund plays a significant role in improving the quality of human resources through scholarship programs, the Aceh Health Insurance, and various skills training programs. However, challenges remain related to public perception, regional fiscal dependence on the Special Autonomy Fund, and inefficient program governance. The Aceh government has made improvements through regulatory strengthening, educational innovations such as the Independent Curriculum, and the enhancement of field-based monitoring and evaluation mechanisms. This study emphasizes the need to strengthen human resource quality as the top priority for Aceh's development, particularly as the Special Autonomy Fund is set to expire in 2028.